Who Should Buy Portfolio Insurance?: Discussion - Schwartz, Eduardo S. (Journal of Finance, 1980)
Eduardo S. Schwartz, Who Should Buy Portfolio Insurance?: Discussion, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 595-596